2023
DOI: 10.3390/ijerph20032702
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior Patterns of the Hungarian Adult Population

Abstract: Background and aim: Nowadays, a high level of sedentary behavior (SB) is an important health issue. Many studies have focused on evaluating the physical activity (PA) level, while evaluation of SB has received less attention. The main goal of the present study is to describe the sedentary lifestyle of the Hungarian adult population and identify the vulnerable groups with high amount of sitting time and the patterns of SB. Another aim of this study is to compare the two types of questionnaires (International Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Dogs motivate their owners to reduce sedentary behaviour and increase physical activity. This finding is important because nowadays a lot of research reports on the spread of sedentary lifestyles, increasing sedentary time, which is a health risk for obesity and cardiovascular diseases [1,19,20].…”
Section: Resultsmentioning
confidence: 95%
“…Dogs motivate their owners to reduce sedentary behaviour and increase physical activity. This finding is important because nowadays a lot of research reports on the spread of sedentary lifestyles, increasing sedentary time, which is a health risk for obesity and cardiovascular diseases [1,19,20].…”
Section: Resultsmentioning
confidence: 95%
“…The prevalence of leisure-time physical exercise among the participants in the current study was 14.8%, which was markedly lower than that in high-income and middle-income countries. In a study conducted on young Europeans from 21 countries, the overall prevalence of leisure-time physical exercise among women was 68.3%, with the highest prevalence in Hungary (95%) [35] and the lowest in Greece (29%) [36]. A study conducted on multiethnic Asian populations revealed that the prevalence of su ciently active women was 82.4% [29].…”
Section: Discussionmentioning
confidence: 99%